A new composite measure of colonoscopy: the Performance Indicator of Colonic Intubation (PICI) - Valori, Roland M.; Damery, Sarah; Gavin, Daniel R.; Anderson, John T.; Donnelly, Mark T.; Williams, J. Graham; Swarbrick, Edwin T. (Endoscopy, 2018)
Background and study aim Cecal intubation rate (CIR) is an established performance indicator of colonoscopy. In some patients, cecal intubation with acceptable tolerance is only achieved with additional sedation. This study proposes a composite Performance Indicator of Colonic Intubation (PICI), which combines CIR, comfort, and sedation.Methods Data from 20 085 colonoscopies reported in the 2011 UK national audit were analyzed. PICI was defined as the percentage of procedures achieving cecal intubation with median dose (2 mg) of midazolam or less, and nurse-assessed comfort score of 1 – 3/5. Multivariate logistic regression analysis evaluated possible associations between PICI and patient, unit, colonoscopist, and diagnostic factors.Results PICI was achieved in 54.1 % of procedures. PICI identified factors affecting performance more frequently than single measures such as CIR and polyp detection, or CIR + comfort alone. Older age, male sex, adequate bowel preparation, and a positive fecal occult blood test as indication were associated with a higher PICI. Unit accreditation, the presence of magnetic imagers in the unit, greater annual volume, fewer years’ experience, and higher training/trainer status were associated with higher PICI rates. Procedures in which PICI was achieved were associated with significantly higher polyp detection rates than when PICI was not achieved.Conclusions PICI provides a simpler picture of performance of colonoscopic intubation than separate measures of CIR, comfort, and sedation. It is associated with more factors that are amenable to change that might improve performance and with higher likelihood of polyp detection. It is proposed that PICI becomes the key performance indicator for intubation of the colon in colonoscopy quality improvement initiatives.